Dextrin, sugar and organic acid profiles of spontaneous and modified gowe: a malted and fermented sorghum beverage from Benin - Vieira-Dalode, Generose (My University, 2015)
Gowe is a traditional Beninese fermented red sorghum beverage made from a blend of malted and precooked nonmalted flour. The main objective of this work was to evaluate the degradation of starch during the production of gowe and to characterise the organic acid and sugar profiles of the product obtained using starter cultures. Inoculation was performed with strains of Lactobacillus fermentum or Weissella confusa and of Kluyveromyces marxianus or Pichia anomala used singly or in combination. Size exclusion chromatography revealed that starch was hydrolysed into high molecular weight dextrins (DP over 35), oligosaccharides and glucose, mainly due to the malting and precooking steps. Glucose was the main free sugar, and lactic acid was the main organic acid. The choice of the inoculation strain directly influenced the acidity but also indirectly the sugar content of the resulting gowe and will thus affect consumer acceptability.
Keywords: Gowe; organic acid; sorghum; starch degradation; sugar.